Analysis of a national difficult airway database. (7th August 2022) - Sajayan, A.; Nair, A.; McNarry, A. F.; Mir, F.; Ahmad, I.; El‐Boghdadly, K.
Summary: Difficult airway management continues to adversely affect patient care and clinical outcomes and is poorly predicted. Previous difficult airway management is the most accurate predictor of future difficulty. The Difficult Airway Society initiated a national airway database to allow clinicians to access details of previous difficult airway episodes in patients issued with a difficult airway alert card. We aimed to analyse this database, reporting patient characteristics, airway management and patient outcomes. We included all living adult patients reported in the first 5 years of the database (n = 675). Clinical airway assessment was reported in 634 (94%) patients, with three or more parameters assessed in 488 (72%). A history of difficult airway was known in 136 (20%) patients and difficult airway management was anticipated in 391 (58%). In all, 75 (11%) patients had an airway‐related critical incident, with 1 in 29 being awoken from anaesthesia, 1 in 34 requiring unplanned or prolonged stay in the intensive care unit and 1 in 225 needing an emergency front‐of‐neck airway or had a cardiac arrest/peri‐arrest episode. Airway‐related critical incidents were associated with out‐of‐hours airway management, but no other associations were apparent. Our data report the first analysis of a national difficult airway database, finding that unanticipated difficult airway management continues to occur despite airway assessment, and the rate of critical incidents in this cohort of patients is high. This database has the potential to improve airway management for patients in the future.